The Communist International :
Russ. ed.: Kommunističeskij Internacional (ZK 16007). - German ed.: Die Kommunistische Internationale (ZO 16050). - French ed.: L'Internationale Communiste (ZK 16001). - Spanish ed.: Internacional Comunista (Zo 16045). - Ital. ed.: L'Internazionale Comunista (ZK 16006).